DKV SEBAGAI PERANCANGAN MEDIA PROMOSI JURUSAN DESAIN KOMUNIKASI VISUAL (DIII) UNDIKSHA BERBASIS WEB - Elly Herliyani; Jajang Suryana (Prasi: Jurnal Bahasa, Seni, dan Pengajarannya, 2015)
The study aimed at designing a Web-based promotion media used for the Department of Visual Communication Design (DIII) UNDIKSHA, as well as to find out and describe the students’ responses towards the implementation of a Web-based promotion media for the Department of Visual Communication Design. This study utilized a research and development method focusing on the implementation of CIPP model (consists of Context, Input, Process and Product) for developing a web design. Try out were conducted by one expert on media and another one expert in the content; three individual try out and eight small groups of the students from the Department of Visual Communication Design were also made as well as 30 respondents were used for field try out selected from the students of Department of Art Education, UNDIKSHA. The precentage score of the media expert judgement towards the web test was about 92.00% which could be categorized as an outstanding score. The percentage score of the content expert was about 86.00% which meant as a ‘good” qualification. The precentage score of the individual try out was about 79.38% which meant as a “fair” category. The percentage score of eight small groups try out was about 72.86% which meant as “fair” category. The precentage score of the field try out was about 86.40% which was classified as “good” category. The precentage score obtained from the responses provided by the students of the Department of Art Education was about 85.07% which was classified as “good” category. Finally, the website of Department of Visual Communication Design, Faculty of Language and Arts at http://dkv.undiksha.ac.id/ was forwarded to the community of Department of Visual Communication Design (DIII) UNDIKSHA, Facebook, and Youtube.Key words: Department of Visual Communication Design, Ganesha University of Education, media, promotion, web.